Perlindungan Hukum Bagi Penyandang Disabilitas Sebagai Korban Penganiayaan dalam Perspektif Hukum Pidana Islam - Rika Risky; Hj. Sahlia (Jurnal Interpretasi Hukum, 2024)
Despite the creation of laws that contain all existing problems, it does not rule out the possibility that crimes will still occur in this world, one of which is persecution. What is more concerning is if the persecution occurs to persons with disabilities, who do not have the ability to protect themselves. This study aims to determine the factors that cause persecution of persons with disabilities, legal protection for persons with disabilities, formulation or form of punishment received by perpetrators of persecution of persons with disabilities as victims of persecution in the perspective of positive law and Islamic criminal law This research uses a type of literature study or normative law, which is a collection of actions related to library data collection. To collect data, this research uses a qualitative approach. The results of data analysis show the factors that lead to the persecution of persons with disabilities, things that are intended to protect persons with disabilities as victims of persecution and the formulation or form of punishment received by the perpetrator in the perspective of positive law and also Islamic criminal law. The implications of this research include several laws and also arguments sourced from the Qur'an and hadith and also the need for awareness from surrounding people and also law enforcement to realize protection for persons with disabilities.